Nanodevices - Editorial - Nezih Pala (Nanomaterials and Nanotechnology)
The race for continuous scaling has been fuelling the electronics industry for the last half a century, allowing unprecedented innovations and achievements. Undoubt‐ edly, silicon and, to some extent, III-V semiconductors have been the front runners of the ever-shrinking electronic devices used in integrated circuits. However, with the recent advances in material synthesis, processing at the nanoscale allowed demonstration of nanoscale devices of previously unimagined materials. With their inherently advantageous properties, nanoscale materials and devices have already been used in numerous applications in diverse fields, including but not limited to bio/chemical sensing, imaging, displaying, quantum computation, communication, energy harvesting and storage, environ‐ mental protection, brain-machine interfaces, neural stimulation and prosthetics, theranostics and artificial organs.